Treatment of non-atopic dermatitis with polarized UV-free polychromatic light: A case report - Leguina-Ruzzi, Alberto (Clin Pract, 2019)
Non-atopic dermatitis is a common inflammatory condition, which is potentially debilitating and can compromise life quality. Polarized ultraviolet-free polychromatic light is used as therapeutic option for the treatment of wound healing and dermatological conditions. It has not yet been tested in the management of non-atopic dermatitis. In this case report, we present a 67- year-old female patient who had suffered with moderate non-atopic dermatitis for the past 20 years, and had undergone multiple treatments during that time without significant improvement or relief from her symptoms. She was treated for six weeks only with daily light therapy applications (10 minutes/area). Our results showed that light therapy offered a significant reduction in erythema of the affected zones with a concomitant reduction in pruritus and dehydration of the skin, without side effects or discomfort.